Answer:
268
Step-by-step explanation:
11/37=credit card
11/37=x/900
900 divided by 37=24.3
24.3 times 11=267.56
round it to 268
Answer:
16
Step-by-step explanation:
Since 2+2 is in parenthesis you do that first. So now you have 8/2(4). 8/2= 4. 4*4 = 16
Answer:
x=6
Step-by-step explanation:
h(x) = -( x-2)^2 +16
We want when h(x) = 0
0 = -( x-2)^2 +16
Subtract 16 from each side
-16 = -( x-2)^2 +16-16
-16 = -( x-2)^2
Divide by -1
16= ( x-2)^2
Take the square root of each side
±sqrt(16) = sqrt(( x-2)^2 )
±4 = x-2
Add 2 to each sdie
2 ±4 = x-2+2
2+4 = x 2-4 =x
6 =x -2 =x
since time cannot be negative
x=6
Answer:
Step-by-step explanation:
Simplifying
2x + 13 = 0
Reorder the terms:
13 + 2x = 0
Solving
13 + 2x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 2x = 0 + -13
Combine like terms: 13 + -13 = 0
0 + 2x = 0 + -13
2x = 0 + -13
Combine like terms: 0 + -13 = -13
2x = -13
Divide each side by '2'.
x = -6.5
Simplifying
x = -6.5